COVID-19 and religious congregations: Implications for spread of novel pathogens. (July 2020) - Quadri, Sayed A.
Highlights: Assembly of the faithful is practiced by many religious faiths and orders. People remain in close proximity during prayer meetings, sometimes for long hours, increasing the transmission risk of novel pathogens. Religious congregations could potentially prove to be transmission and dispersal hubs of such pathogens as seen with COVID-19 hotspots. Suspension of communal gatherings must be promptly done as a preventive strategy whenever novel pathogens emerge, in order to contain their spread. An international regime of containment measures with regard to suspension of religious congregations during infectious disease outbreaks must be devised. Abstract: The COVID-19 pandemic is ravaging the world. A principal preventive strategy is practicing social distancing. Congregations of the faithful at the local and transnational levels are strongly recommended by several world religions and religious orders, however, a gathering of large numbers of people in close approximation could be fertile ground for the spread of novel pathogens. The refusal to suspend such gatherings could lead to potential widespread dispersal of infections.